Development of neural responses to hearing their own name in infants at low and high risk for autism spectrum disorder - Melda Arslan; Petra Warreyn; Nele Dewaele; Jan R. Wiersema; Ellen Demurie; Herbert Roeyers (Developmental Cognitive Neuroscience, 2020)
The own name is a salient stimulus, used by others to initiate social interaction. Typically developing infants orient towards the sound of their own name and exhibit enhanced event-related potentials (ERP) at 5 months. The lack of orientation to the own name is considered to be one of the earliest signs of autism spectrum disorder (ASD). In this study, we investigated ERPs to hearing the own name in infants at high and low risk for ASD, at 10 and 14 months. We hypothesized that low-risk infants would exhibit enhanced frontal ERP responses to their own name compared to an unfamiliar name, while high-risk infants were expected to show attenuation or absence of this difference in their ERP responses. In contrast to expectations, we did not find enhanced ERPs to own name in the low-risk group. However, the high-risk group exhibited attenuated frontal positive-going activity to their own name compared to an unfamiliar name and compared to the low-risk group, at the age of 14 months. These results suggest that infants at high risk for ASD start to process their own name differently shortly after one year of age, a period when frontal brain development is happening at a fast rate. Keywords: Social development, Own name, Event-related potentials, Autism spectrum disorder, High-risk siblings, Infants